Investigation of corrosion damage of hydration aluminium alloys at full-scale accelerated tests - Laptev, Anatoly; Kurs, Maria; Lonskaya, Natalya; Davydov, Dmitry; Averina, Alena (International Journal of Engineering and Technology, 2019)
The results of the study of hydrogen penetration in corrosion of aluminum alloys of eight alloying systems are presented. Tests were carried out for four years with additional irrigation with chloride solutions in a moderately warm climate. It is shown that intensive hydrogenation of the alloy occurs during corrosion. The amount of hydrogen in the alloy is determined by the type of corrosion - with intercrystalline corrosion, hydrogen penetration is more intense than with pitting and delaminating corrosion. The mechanism of hydrogenation of alloys is proposed. The change in the energy of the aluminum crystal in the occlusion of atomic hydrogen and the formation of hydrogen molecules is determined by quantum chemical calculations. The relationship between the plasticity of the tested alloys of aluminum alloys and the intensity of hydrogen saturation is shown.